2021
DOI: 10.1111/jnc.15284
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota‐gut‐brain axis as a regulator of reward processes

Abstract: The reward system is a set of neuronal structures responsible for the processing of a number of psychological components, such as 'wanting', 'liking' and associative learning (Berridge & Robinson, 2003).These three processes occur together, 'wanting' dominates the initial appetitive phase, 'liking' dominates the consummatory phase, and learning occurs through the reward-behavioural cycle (Berridge et al., 2016). Both phenomena are underpinned by different brain circuits and neurotransmitter systems. The 'wanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 428 publications
(466 reference statements)
0
56
0
Order By: Relevance
“…In addition, over recent decades, a new decisive player has emerged in this equation [ 57 ]. Living gut microorganisms and their bioactive metabolites, including short-chain fatty acids (SCFAs) and conjugated fatty acids among others, and their neuroactive metabolites, such as serotonin (5-hydroxytryptamine; 5-HT) and γ-aminobutyric acid (GABA), are released in the bloodstream and can modulate the CNS directly or indirectly by affecting the ANS [ 58 , 59 , 60 ]. Hence, changes in enteric neuron activity will be perceived by the vagus nerve to modulate, among other physiological aspects, appetite, satiety, stress, and mood.…”
Section: Gut Microbiota: a Key Player In The Regulation Of Eating Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, over recent decades, a new decisive player has emerged in this equation [ 57 ]. Living gut microorganisms and their bioactive metabolites, including short-chain fatty acids (SCFAs) and conjugated fatty acids among others, and their neuroactive metabolites, such as serotonin (5-hydroxytryptamine; 5-HT) and γ-aminobutyric acid (GABA), are released in the bloodstream and can modulate the CNS directly or indirectly by affecting the ANS [ 58 , 59 , 60 ]. Hence, changes in enteric neuron activity will be perceived by the vagus nerve to modulate, among other physiological aspects, appetite, satiety, stress, and mood.…”
Section: Gut Microbiota: a Key Player In The Regulation Of Eating Behaviourmentioning
confidence: 99%
“…However, fewer studies have been conducted to answer how the microbiota might influence addiction-related behaviors, such as “food/eating addiction”. Even though the research to date is not complete, increasing evidence shows how microbiota dysbiosis is implicated in the development of these maladaptive habits [ 8 , 10 , 58 , 168 , 169 , 170 , 171 , 172 ] ( Figure 3 ). Considering this, all factors affecting the “healthy” composition of the GM, including host genetics [ 173 , 174 ], diet [ 175 , 176 ], age [ 177 , 178 ], mode of birth [ 179 , 180 ], and antibiotics intake [ 181 , 182 ], among others, can shape GM and ultimately trigger an abnormal eating behaviour.…”
Section: Interrelationship Between Gut Microbiota and Food Addictionmentioning
confidence: 99%
“…Gut microbiome plays an essential role in food digestion, xenobiotic metabolism, and regulation of innate and adaptive immunological processes (Bishehsari et al 2017 ; Cryan et al 2019 ). Indeed, dysbiosis, a term representing a loss or reduction of beneficial bacteria and accumulation of pathogenic ones (Belizário and Faintuch 2018 ), has been associated with dysregulation of food intake and energy homeostasis (Romaní-Pérez et al 2021 ; Woźniak et al 2021 ) and implicated in a myriad of central nervous system (CNS) disorders such as anxiety and depression (Cryan et al 2019 ; Knudsen et al 2021 ; Poluektova et al 2021 ), stroke (Yamashiro et al 2021 ), multiple sclerosis (Ullah et al 2021 ), Parkinson’s disease (Tizabi et al 2021a ), autism (Kong et al 2021 ), schizophrenia (Kelly et al 2021 ), aging (Li et al 2021 ; van Krimpen et al 2021 ), cognitive dysfunction (Cryan et al 2019 ; Cowan and Cryan 2021 ; Li et al 2021 ), Alzheimer’s disease (Giovannini et al 2021 ; Jiang et al 2021 ), and even substance abuse (Meckel and Kiraly 2019 ; García-Cabrerizo et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dysbiosis due to alcohol abuse may be a contributing factor to AUD (Engen et al 2015 ; Bishehsari et al 2017 ). Thus, alcohol-induced changes in the gut microbiota may contribute not only to development of alcoholic liver disease, but also to a variety of CNS disorders (Engen et al 2015 ; García-Cabrerizo et al 2021 ). Indeed, it has been suggested that use of probiotic might be of potential use in prevention and treatment of alcohol-associated pathologies (Engen et al 2015 ; Lowe et al 2018 ; Rodriguez-Gonzalez and Orio 2020 ; Carbia et al 2021 ; Gupta et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that there is a bidirectional communication system between gut microbiome and brain, which is known as the microbiomegut-brain axis (MGBA) (Dinan and Cryan, 2017). Increasing evidence revealed the role of intestinal microbial community in neuropsychiatric diseases (Burokas et al, 2015), including reward process and substance use disorders (Garcia-Cabrerizo et al, 2021). It has been found that the composition and diversity of gut microbiome in substance-addicted individuals changed remarkably (Meckel and Kiraly, 2019).…”
Section: Introductionmentioning
confidence: 99%